Learning Outlook 97 : e-mailing (ViaGrafix OklahomaUS, 1998)
Tutorial provides extensive coverage of the e-mail features of Outlook 97. Includes topics such as: setting up e-mail services; receiving and viewing new messages; replying to an e-mail message; deleting a message; storing messages; defining the message options; and examining the recalling feature.
Located in the Learning Resource Centre